Archive, narrative, and loss - Strowe, Anna (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
This article explores notions of loss in the archive through examples of archival materials related to translation, and the framework of narrative theory. Loss is seen as both a preliminary state prompting research and a result of research. Initially this article looks at these types of loss from a less theoretical perspective, before turning to sociological narrative theory as a conceptual framework that can both describe those types of loss and explain broader issues that arise in archival work, which are argued to be forms of narrative loss. Some existing discussions of archival work touch on the idea of narrative, but usually not in a specific enough way to provide a solid framework for the analysis and comparison of narratives themselves. By incorporating the narrative theory elaborated by Somers and Gibson (1994) and brought into translation studies by Baker (2006), I begin to explain how a narrative approach can both account for obvious types of loss and be used to conceptualize other forms of loss that occur in the process of preservation, transmission, and interpretation of archives.